Examination of Changes in Infection Rates in a Restructured Anaesthesia Intensive Care Unit: A Retrospective Study - Deniz, Ahmet; Erhan, Omer Lutfi; Bayar, Mustafa Kemal; Karatepe, Umit; Demirel, Ismail (Aves, 2017)
Objective: This retrospective study aimed to evaluate the effect of a restructured anaesthesia intensive care unit (ICU) on changes in infection rates and infections. Methods: Organisational restructuring was done in the anaesthesia ICU of Firat University Hospital after it was relocated on 14 March 2012. This study was designed to investigate the effect of restructuring on infection rates through a comparison of periods encompassing one year before relocation and one year after relocation. Nosocomial infections were diagnosed according to modified Centers for Disease Control and Prevention (CDC) criteria. In total, 406 patients who were over 18 years old and admitted to the ICU were included; they were hospitalised for 48 h or longer and had non-infectious diseases according to physical examination, laboratory and culture results on admission. The data of 214 patients (Group A) and 192 patients (Group B) were examined. Results: Parameters such as age, gender, primary diagnosis and mean GCS score at admission and mean duration of hospitalisation showed no effect on the rates of infection, but rates of total infection (41.1% vs. 25%), urinary (18.7% vs. 10.4%) and VIP (32.7% vs. 14.6%) were detected in Groups A and B. Statistically significant differences were found for the causative pathogens Pseudomonas (15.4% vs. 6.8%), Acinetobacter (18.2% vs. 12%) and Escherichia (8.9% vs. 2.1%); the mean duration of mechanical ventilation (15.01 +/- 16.681 vs. 12.22 +/- 17.595) and discharge with improvement (31.8% vs. 44.3%). Conclusion: We detected that restructuring (such as acclimatization, educated staff, hepa filter) caused a significant decline in infection rates. Because ICU staff may be a major cause of infection, we believe that providing education and conducting effective surveillance programs will be the most important factors for reducing infection rates.
Keywords: ICU; acclimatisation; HEPA filter